Jovens LGBTQIA+ negros/as e as resistências aos neoconservadorismos: narrando dissidências - Jaime Peixoto da Silva (2022)
The strengthening of neoconservatism in the last decade has intensified racism and violence, tensioning the debate around disputes between life and death, between security and vulnerability. So, in what ways can refusals to the trivialization of dissident lives be produced? This work deals with an investigation that focuses on life narratives by inviting a group of three black LGBTQIA+ young people living in the city of Belo Horizonte to say how they create ways of experiencing their gender, their sexuality and their race in times of political neoconservatism and morals. The aim is to find out in what ways these young dissidents have managed/claimed their appearance in the public space in times of a strengthening of the conservative and precarious machinery of dissident lives and what are the effects of this on their ethical modes of existence. The strategies used by research participants to create more viable ways of life were understood in this thesis in terms of what Foucault (1984) called modes of existence, that is, “the way in which subjects submit themselves more or less completely to to a principle of conduct; by which they obey or resist an interdiction or a prescription; by which they respect or neglect a set of values” (FOUCAULT, 1984, p.26) and invent strategies to live. These are ethical behaviors that show the subjects' relationship with the norm, by engendering resistance to the rules and moral values ​​of society, and also with their relationship with themselves, by creating possibilities for resistance.